IMPLEMENTATION OF ACCOUNTING SYSTEM BASED ON MICROSOFT ACCESS IN PT. BATAM FLOORING SYSTEM - Ivone Ivone; Ivy Lee (Universitas Internasional Batam, 2022)
One of the MSMEs in Batam named PT. Batam Flooring System does not have a proper accounting system. PT. Batam Flooring System also does not make its own company reports but relies on the services of a tax consultant. Therefore, the purpose of this community service is to help PT. Batam Flooring System to have financial statement reporting with a good system-based accounting system such as Microsoft Access. The method of data collection is using methods of interview, observation, and documentation. The result of the community’s service is a Microsoft Access accounting system that will be implemented at PT. Batam Flooring System and is expected to be useful and able to assist the recording of PT. Batam Flooring System. There are also recommendations for further community service to provide innovations and solutions that are even more useful and attractive to other MSMEs.